2019
DOI: 10.1002/ejic.201801231
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Mesoporous ZnO@BMMs with Strong Fluorescence and High Loading Capacity for Controlled Drug Delivery

Abstract: Multifunctional mesoporous ZnO@BMMs were prepared via a facile and reliable post treatment, in which the influence of various parameters, including the amount of ZnCl 2 doping, the different anions of the zinc salt, and the roasting temperature, on their structure, properties, and fluorescence performance were investigated by XRD, SEM, TEM, EDS, DLS, XPS, BET, PL, UV, and TGA/DTG. The drug loading and release performance was explored by using ibuprofen (IBU) as a model drug. The results showed that the ZnO@BMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The drug delivery behaviors of the selected CBI as a drug carrier were shown in Figure . As can be seen in Figure A, the IBU loading capacity of CBI rapidly reached 131.4 mg g −1 and then run up to 154.3 mg g −1 , indicating that CBI had the fast adsorption ability, due to the better IBU‐diffused property in the bimodal mesoporous structures . Figure B showed the IBU‐released behaviors of CBI, which well fitted the exponential equation with high coefficiency of R 2 =0.985, as follows: truey=-40.51×e-x149.2)+43.57 …”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…The drug delivery behaviors of the selected CBI as a drug carrier were shown in Figure . As can be seen in Figure A, the IBU loading capacity of CBI rapidly reached 131.4 mg g −1 and then run up to 154.3 mg g −1 , indicating that CBI had the fast adsorption ability, due to the better IBU‐diffused property in the bimodal mesoporous structures . Figure B showed the IBU‐released behaviors of CBI, which well fitted the exponential equation with high coefficiency of R 2 =0.985, as follows: truey=-40.51×e-x149.2)+43.57 …”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, we found that the MSE method was very useful to remove of CTAB from intermediate than MSI and MSA methods. Overall, these observations suggest the successful introduction of CQDs to BMMs …”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…While, the ZnO/BMMs composite was successfully synthesized via a facile and reliable post treatment, which could be used as a carrier for ibuprofen delivery, showing high loading capacity (around 250 mg/g) and an excellent sustained release behavior along with strong fluorescence. [25,26] These results demonstrated that BMMs would be a good selection as a support. Alizarin red dye (1,2-dihydroxy-9,10-anthraquinonesulfonic acid sodium salt, C 14 H 7 NaO 7 S, abbreviated as AR), as an industrially important synthetic dye from anthraquinone family, is widely used in textile industries since ancient times.…”
Section: Introductionmentioning
confidence: 73%